2002
DOI: 10.1002/art.10453
|View full text |Cite
|
Sign up to set email alerts
|

Statistical presentation and analysis of ordered categorical outcome data in rheumatology journals

Abstract: Objective. To assess the appropriateness of presentation of summary measures and analysis of ordered categorical (ordinal) data in three rheumatology journals in 1999, and to consider differences between basic and clinical science articles. Methods. Six hundred forty-four full-length articles from the 1999 editions of 3 rheumatology journals were evaluated for inclusion of an ordinal outcome. Articles were classified as basic or clinical science, and the appropriateness of presentation and analysis of the ordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…We defined appropriate presentation and analysis methods of ordinal outcome data as conforming to the recommendations summarized in Table 1 5,18,25,26 . A veterinary dermatologist (JDP) and a statistician (JNG) classified articles as reporting either appropriate or inappropriate presentation methods and as reporting either appropriate or inappropriate analysis methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined appropriate presentation and analysis methods of ordinal outcome data as conforming to the recommendations summarized in Table 1 5,18,25,26 . A veterinary dermatologist (JDP) and a statistician (JNG) classified articles as reporting either appropriate or inappropriate presentation methods and as reporting either appropriate or inappropriate analysis methods.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical outcomes measured with ordinal scales are often presented and analysed with inappropriate statistical methods in the medical literature. In the fields of anaesthesia, rheumatology, and nursing, several studies indicated that ordinal data were presented appropriately in only 39–49% and analysed appropriately in 57–63% of journal articles 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…Many research fields regularly use such approaches to assess outcomes with multiple levels, especially when they are ordinal in nature (e.g, outcomes after birth, pain management, rheumatology and surgery). [8][9][10][11] This approach is distinct from the practice of using so-called "surrogate outcomes", in which binary outcomes are also replaced, for example, by a biomarker. 12 This practice is debated, primarily as the clinical relevance is often unclear.…”
Section: Beyond the Binary Outcomementioning
confidence: 99%
“…It is not uncommon for studies using ordinal data to be published despite using incorrect statistical methods. For example, in the medical literature, ordinal data were presented appropriately in only 39-49% of relevant papers and analysed appropriately in only 57-63% (Avram et al 1985;LaValley and Felson 2002;Jakobsson 2004;Jakobsson and Westergren 2005;Plant et al 2007).…”
mentioning
confidence: 99%